2014
DOI: 10.1007/s00210-014-1039-4
|View full text |Cite|
|
Sign up to set email alerts
|

Rat β3-adrenoceptor protein expression: antibody validation and distribution in rat gastrointestinal and urogenital tissues

Abstract: β3-Adrenoceptors play important roles in the regulation of urogenital and probably gastrointestinal function. However, despite recent progress, their detection at the protein level has remained difficult due to a lack of sufficiently validated selective antibodies. Therefore, we have explored the selectivity of two antibodies for the detection of rodent β3-adrenoceptors in immunoblots and immunohistochemistry. Of two reportedly promising candidates, antibody AB15688 did not exhibit subtype selectivity in immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…In combination with previous observations that a β 3 -AR antibody was non-selective in Western blot experiments but selective when used for immunohistochemistry (Cernecka et al, 2014), these data suggest that antibodies can display different degrees of selectivity in different assays, different species or tissues and when different types of specimens, such cells, homogenates or tissue sections, are being evaluated. This phenomenon is likely related to the fact that, depending on the application and experimental conditions, the probed epitopes can be linear or three-dimensional, completely exposed and completely or partially masked by post-translational modifications.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In combination with previous observations that a β 3 -AR antibody was non-selective in Western blot experiments but selective when used for immunohistochemistry (Cernecka et al, 2014), these data suggest that antibodies can display different degrees of selectivity in different assays, different species or tissues and when different types of specimens, such cells, homogenates or tissue sections, are being evaluated. This phenomenon is likely related to the fact that, depending on the application and experimental conditions, the probed epitopes can be linear or three-dimensional, completely exposed and completely or partially masked by post-translational modifications.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, selective antibodies that detect endogenous GPCRs can be essential for the study of these receptors (Gupta and Devi, 2006, Talmont et al, 2012). Several lines of evidence, however, suggested that many commercially available antibodies directed against GPCRs, such as histamine receptors, adrenoceptors or chemokine receptors, lack sufficient selectivity (Hamdani and van der Velden, 2009, Jensen et al, 2009, Pradidarcheep et al, 2009, Berahovich et al, 2010, Beermann et al, 2012, Bohmer et al, 2014, Cecyre et al, 2014, Cernecka et al, 2014, Talmont and Mouledous, 2014). Accordingly, it has been proposed that receptor antibodies should be validated by at least one of the following techniques: a) disappearance of staining in knock-out animals of the target receptor, b) reduction of staining upon knock-down approaches such as siRNA treatment, c) selectivity of staining in immunoblots or immunocytochemistry for the target receptor vs. related subtypes when expressed in the same cell line and/or d) antibodies raised against multiple distinct epitopes of a receptor yielding very similar staining patterns (Michel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…β3-AR KO are unsuitable to explore target selectivity of sc-50436 as the position of the cassette leading to disruption of the β3-AR gene may cause a functional knockout while still allowing for expression of the C-terminus of the receptor (Cernecka et al 2014a). As shown in Online Resource 2, Western blot analysis of homogenates from B16F10 cells revealed that sc-50436 labeled a major band and a faint second band.…”
Section: Validation Of β-Ar Antibodiesmentioning
confidence: 97%
“…For example, the commercial antibody sc-1473, used to show induction of the β3 by norepinephrine, 10 is not selective for the β3 in immunoblots. 11, 12 Monoclonal antibody Mab72c was developed by immunizing rats with CHO cells expressing the human β3-AR at 3000 fmol/mg. 9 This antibody appears to be the one used in a key study to suggest robust upregulation of the β3-AR in immunoblots of failing human myocardium, with diffuse cytoplasmic expression in all visualized heart failure (HF) myocytes.…”
Section: To the Editormentioning
confidence: 99%